High nucleotide divergence in a dimorphic parasite with disparate hosts - Kathirithamby, Jeyaraney; Gillespie, Joseph J.; Jimenez-Guri, Eva; Cognato, Anthony I.; Johnston, J. Spencer (Zootaxa, 2007)
Morphologically cryptic male C. fenyesi sensu lato are found parasitic in different ant hosts over a wide geographical range. We use ribosomal DNA (rDNA) primary sequence and predicted rRNA secondary structure to compare between the second expansion segment (D2) of the nuclear large subunit rDNA (28S) and the entire nuclear small subunit rDNA (18S) of the male and the sexually dimorphic, neotenic female of Caenocholax fenyesi waloffi Kathirithamby & Johnston from Los Tuxtlas, Mexico, with that of the morphologically identical male C. f. texensis Kathirithamby & Johnston (Myrmecolacidae) from Texas, USA. In Los Tuxtlas the male C. f. waloffi parasitizes the ant, Dolichoderus bispinosus Olivier, while the female parasitizes the cricket, Macroanaxipha macilenta (Saussure). In Texas, the male C. f. texensis parasitizes the red imported fire ant, Solenopsis invicta Buren. The compared sequences show similar unusual secondary structures in the rRNA variable regions, but with approximately 14% overall divergence between Mexican and Texan specimens (15.5% divergence after correction for multiple substitutions). Our findings open a new opportunity in evolutionary biology to investigate speciation under a mechanism of morphological stasis and high genetic divergence in a unique parasite that is not only profoundly sexually dimorphic but wherein the sexes specialize in entirely different niches (hosts).